The silver eyes - Cawthon, Scott, 1971-; Breed-Wrisley, Kira (Scholastic, Inc., 2016)
Ten years after the murders at Freddy Fazbear's Pizza, Charlie and her childhood friends get together on the anniversary of the event at the abandoned pizza place to find that the four animatronic entertainment mascots have changed.
Accelerated Reader
Keywords: Robots -- Juvenile fiction; Pizzerias -- Juvenile fiction; Survival -- Juvenile fiction; Zombies -- Juvenile fiction; Young adult fiction; Robots -- Fiction; Pizzerias -- Fiction; Horror stories; Robots -- Fiction; Pizzerias -- Fiction; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Horror; JUVENILE FICTION / Media Tie-In.; Horror fiction; Horror fiction